Identification of chemical residues of oxytetracycline in the bovine fresh meat, destined for human consumption in the department of Córdoba - Negrete Diaz, Claudia de Jesus; Segura Castro, Eliana Paola; Torres Sibaja, Maria Elena; Badel Causil, Jose Anibal (Revista Colombiana de Investigaciones Agroindustriales, 2017)
The investigation allowed identifying the presence of antibiotic oxytetracycline residues in fresh meat, commercialized for human consumption in the department of Córdoba (Colombia). (81) randomly collected samples of diaphragmatic muscle in three department stores, two of which belong to the category of self-consumption located in the municipalities of the Dominican Republic (Coproexcal) and Montelíbano (Incarsan) and one of the National category located in the Municipality of Cereté (Frigocer - Expocol), covering a large part of the population of Córdoba. The HPLC high performance liquid chromatography method was used to identify oxytetracycline residues in fresh beef, these results were compared to the maximum parameters allowed under Colombian legislation and the Codex Alimentarius. It was found that 4.94% (n = 4) of the analyzed samples presented detectable levels of oxytetracycline, however they did not exceed the limits acceptable for commercialization at the national level. The sex and the age of the sampled animals were determinant in the obtained results, the samples with detection of oxytertacycline corresponded to females older than 3 years, coming from the municipalities of Monteria, Montelíbano and Buenavista. It is verified that the weight loss of beef in beef studied was low, it is necessary to continue to grow all the products of primary production, good cattle practices and good practices in the use of veterinary drugs with innocuous food to the final consumer in the department of Cordoba.